Using Spectrum-Effect Relationships Coupled with LC–TOF–MS to Screen Anti-arrhythmic Components of the Total Flavonoids in Hypericum attenuatum Extracts. (12th December 2020) - Feng, Yufei; Teng, Lin; Wang, Yanli; Gao, Yanyu; Ma, Yuxuan; Zhou, Haichun; Cai, Guofeng; Li, Ji
Abstract: This research explored the HPLC fingerprints of Hypericum attenuatum Choisy, which has anti-arrhythmic activity. HPLC was adopted to perform a determination of chemical fingerprints of H. attenuatum specimens acquired through seven distinct sources. The anti-arrhythmic activity of each H. attenuatum sample was obtained through pharmacodynamics experiments in animals. A regression analysis and correlation analysis were utilized to calculate the relationship of the peak and pharmacological effectiveness with the identified peak. Peaks numbered 5, 7, 13 and 14 in the fingerprint were regarded as the likely anti-arrhythmic agents. The fingerprint was compared with reference standards for identification of the correlative peaks. Liquid chromatography–time-of-flight–mass spectrometry was applied to identify its structure. As a consequence, a universal model was established for the utilization of HPLC to investigate anti-arrhythmic activity and the spectrum-effect relationship among H. attenuatum . This model is available for the discovery of the major bioactive constituents of Hypericum .